Implementasi Model Pembelajaran Multiple Intelligences Dalam Menyongsong Era Super Smart Society 5.0 - Ety Kurniyati; Asep Abdurrohman (Universitas Muhammadiyah Tangerang, 2022)
One of the problems of progress in the field of education is the view of intelligence. The implementation of education in Indonesia focuses more on the cognitive field so that other intelligences are forgotten to be developed optimally. Students must have supporting abilities to face the era of society 5.0, of course, obtained from education that facilitates the development of all intelligences. The purpose of writing this article is to describe multiple intelligences from the point of view of neuroscience, the learning model of multiple intelligences, and the benefits for students to be ready to face the era of society 5.0. The method used is theoretical research, the type of descriptive research, data analysis through interactive models, and data obtained from the literature. The results of the discussion are: (1) neuroscience can explain scientifically multiple intelligences; (2) the multiple intelligences learning model consists of approaches, strategies, methods, techniques and methods; (3) multiple intelligences can prepare students to face the era of society 5.0. The conclusion from writing this article is that the multiple intelligences-based learning model can prepare students to face the era of society 5.0 so that it is hoped that learning will not only focus on cognitive aspects